IMAGING EVALUATION OF PAEDIATRIC ORBITAL PATHOLOGIES - Koc, Gonca; Doganay, Selim; Ciraci, Saliha; Dogan, Mehmet Sait; Karakukcu, Musa; Evereklioglu, Cem; Coskun, Abdulhakim (Journal of Ayub Medical College Abbottabad, 2017)
The orbital pathologies commonly detected during the childhood period substantially differ from the lesions that arise in adult orbit. The advance in imaging modalities including computed tomography (CT) and particularly magnetic resonance imaging (MRI) might enable the radiologists and clinicians who would be involved in either medical or surgical care of orbital pathologies, to confidently establish a definite diagnosis prior to histopathologic examination. The purpose of this pictorial assay is to present relatively common paediatric orbital pathologies with regard to CT and MRI findings. Keywords: Orbit; magnetic resonance imaging; computed tomography; ultrasonography; Paediatrics